THE LINGUISTIC IDENTITY OF ARABIC IN THE AGE OF ARTIFICIAL INTELLIGENCE: BETWEEN THREAT AND RECONFIGURATION - Nabila Nabil Tokhy Kandil (ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2025)
The Arabic linguistic field is witnessing rapid transformations due to the widespread use of Artificial Intelligence, particularly in machine translation and generative language models. These technological developments raise questions regarding their impact on the structure of Arabic and its stylistic and rhetorical features, and whether they contribute to the emergence of a hybrid language at the expense of the traditional linguistic identity. This study aims to analyze the linguistic and cultural dimensions of AI’s influence, in order to distinguish between potential threats and possible opportunities. The findings indicate that relying on AI models trained mainly on foreign data results in the simplification of Arabic linguistic structures. However, establishing a comprehensive Arabic digital content and developing Arabic-oriented language models can guide AI to reshape the Arabic language in a way that suits the digital context while preserving its cultural and rhetorical identity.